Internal crisis communication: exploring antecedents and consequences from a managerial viewpoint - Hamid, Aida Suhana; Mohamad, Bahtiar; Ismail, Adibah (Frontiers in Communication, 2024)
Over the past decade, internal crisis communication (ICC) has experienced significant advancements and transformations due to various factors, including technological developments, changing communication landscapes, and the increasing need for effective crisis management within organizations. Crises have impacted organizations differently worldwide, placing management under tremendous pressure to communicate their decisions to employees and provide encouraging messages amidst the uncertainty. Based on prior theoretical and empirical research, this paper explores the causeand-effect relationships between the antecedents of internal crisis communication and their consequences from a managerial perspective in the workplace. This research proposes a new conceptual framework that integrates multiple key factors in internal crisis communication, offering a comprehensive approach to studying the interplay between antecedents and consequences. The framework specifically examines how three antecedents -safety culture, work engagement, and leadership effectiveness -influence and interact with two consequences: perceived organizational performance and employee commitment. By synthesizing these diverse elements into a cohesive model, this framework contributes to the literature on internal crisis communication in several ways. First, it enables the examination of both direct and indirect relationships between antecedents and consequences, potentially revealing new insights into the complexities of crisis communication dynamics. Second, it provides a structured approach for future empirical studies to test and validate these relationships in various organizational contexts. Lastly, it offers a research agenda to advance the study of internal crisis communication, aiding both academics and practicing managers in developing strategies to mitigate uncertainty during crises.